Effect of Moderate Exercise on the level of DHEAS hormone and lymphocyte apoptosis in healthy subjects. - Jassim, Huda A.; Ja’ffar, Israa F.; Hussein, Alaa G. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Physical exercise is essential for performance of the immune system. The integrity of immune response is dependent on the intensity and duration of the exercise performed. During exercise the metabolic and hormonal changes that occurred can induce lymphocyte apoptosis. Dehydroepiandrosteron sulphate (DHEAS) is one of the hormones that is affected by exercise, it is an androgen released from the adrenal cortex in response to adrenocortiocotropin releasing hormone (ACTH). DHEAS is regarded as an anti-aging hormone; it is primarily immune enhancing, providing some degree of counterbalance to the potentially detrimental effects of catecholamine and cortisol which are immunosuppressive if chronically elevated, it also had a role in the elimination of harmful lymphocytes which may give rise to chronic inflammation and possibly to autoimmunity. Methods: Sixty healthy subjects were involved in this study with a mean age of (37.05 ± 13.02) year. They were subjected to moderate exercise session which lasted for 60 min and repeated 3 times per week for 3 months. The exercise intensity was 50-60% of heart rate reserve (according to Karvonen formula). Two exercise stages were performed; the first stage include 30 minute of physical activity program and the second stage include 30 minute of treadmill exercise. Blood samples were collected before and after exercise to examine its effect on the level of DHEAS hormone and apoptosis of peripheral blood lymphocyte. Results: This study showed significant increment (P < 0.05) in the level of DHEAS hormone and the percentage of lymphocyte apoptosis after exercise in comparison to pre exercise values for each week along the period of the test.Three months exercise showed a significant correlation with the levels of DHEAS hormone (P= 0.000, r= 0.75), and with percentage of lymphocyte apoptosis (P = 0.001, r= 0.701). Conclusion: in this prospective study, following moderate exercise for three months; there was increase in the percentage of periphral blood lymphocyte apoptosis and increased level of DHEAS hormone in the first two months while in the third month this anti aging hormones had reached to a steady state after the subjects get trained to exercise.